PELATIHAN SOFTWARE COMFAA BAGI MAHASISWA TEKNIK SIPIL DI KOTA SEMARANG - Agus Muldiyanto,; Mudjiastuti Handajani,; Adolf Situmorang,; Purwanto, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Technological developments really help a civil engineering graduate in designing in the civil engineering field. There are a lot of software that can be used to design runway pavement thicknesses, one of them is COMFAA. In this service activity, the service team conducted training about the calculation of the runway pavement thickness at the airport using COMFAA software for civil engineering students and construction workers. The purposes of this service activity are to give deep understanding about the design of pavement layers on airport runways, to develop knowledge in pavement thickness designs, and to enhance the engineering student’s competence in using COMFAA to plan airport pavement layers. The implementation of this service was carried out in Semarang for Civil Engineering students and Construction Actors. The result was an understanding enhancement of runway pavement analysis from 0% to 77%.